Individual Muscle Contributions to Push and Recovery Subtasks during Wheelchair Propulsion - Rankin, Jeffery W. (2011)
Manual wheelchair propulsion places considerable physical demand on the upper extremity and is one of the primary activities associated with the high prevalence of upper extremity overuse injuries and pain among wheelchair users. As a result, recent effort has focused on determining how various propulsion techniques influence upper extremity demand during wheelchair propulsion. However, an important prerequisite for identifying the relationships between propulsion techniques and upper extremity demand is to understand how individual muscles contribute to the mechanical energetics of wheelchair propulsion. Therefore, the purpose of this study was to use a forward dynamics simulation of wheelchair propulsion to quantify how individual muscles deliver, absorb and/or transfer mechanical power during propulsion. The analysis showed that muscles contribute to either push (i.e. deliver mechanical power to the handrim) or recovery (i.e. reposition the arm) subtasks, with the shoulder flexors being the primary contributors to the push and the shoulder extensors being the primary contributors to the recovery. In addition, significant activity from the shoulder muscles was required during the transition between push and recovery, which resulted in increased co-contraction and upper extremity demand. Thus, strengthening the shoulder flexors and promoting propulsion techniques that improve transition mechanics have much potential to reduce upper extremity demand and improve rehabilitation outcomes.